204k views
0 votes
-6 x + 4 = -20
and add your steps to solve

2 Answers

5 votes

Answer:

-4

Explanation:

-6x+4=-20

-6x+24 (add like variables)

-4 (divide by -6)

User AusCBloke
by
6.1k points
4 votes

Answer:

x = 4

Explanation:

Isolate the variable, x. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS. PEMDAS is the order of operation, and stands for:

Parenthesis

Exponents (& Roots)

Multiplication

Division

Addition

Subtraction

First, subtract 4 from both sides of the equation:

-6x + 4 (-4) = -20 (-4)

-6x = -20 - 4

-6x = -24

Next, divide -6 from both sides of the equation:

(-6x)/-6 = (-24)/-6

x = (-24)/(-6)

x = 4

x = 4 is your answer.

~

User Dhirendra
by
6.6k points